1976
DOI: 10.1172/jci108421
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of technetium-99m stannous pyrophosphate and thallium-201 scintigraphy of acute anterior myocardial infarcts in dogs.

Abstract: A B S T R A C T In 17 dogs with acute myocardial infarcts produced by ligation of the proximal left anterior descending coronary artery, a comparative study was made of myocardial scintigrams obtained with technetium-99m stannous pyrophosphate ("mTc-PYP) and thallium-201 ('Tl), tissue levels of 'Tc-PYP and 'Tl uptake, histopathologic alterations, and regional myocardial perfusion measured with radioactive microspheres. 9 of the 10 hearts examined histologically had transmural infarcts with outer peripheral, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Hearts with proximal LAD occlusion had transmural anterior infarcts with histopathologically distinct central and peripheral regions as previously described (3,4).…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations
“…Hearts with proximal LAD occlusion had transmural anterior infarcts with histopathologically distinct central and peripheral regions as previously described (3,4).…”
Section: Methodsmentioning
confidence: 62%
“…A more detailed analysis was undertaken of the distribution of 99mTc-P and calcium in infarcted myocardium. Study of corresponding histologic sections allowed assignment of samples for tissue assay to the various histopathologically defined infarct zones (3,4). Total number of infarct samples assayed for each dog ranged from 15 to 35.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In each dog in this group the residual blood flow in the center of the infarct was 3% or more of normal myocardial blood flow. cells, but do not accumulate in normal myocardial cells.8' 12-14 Although both experimental" and clinical15 studies have raised the possibility that "mTc-PYP can accumulate to a slight degree in reversibly damaged myocardial cells, accumulation of "9mTc-PYP generally indicates irreversible myocardial damage.6 7,13 A recent study from our laboratory using scanning electron microscopy with elemental x-ray dispersive microanalysis indicated that substantial levels of iodine were measured in myocardial cells within the infarcted region, but no iodine was detected in normal myocardium. 15 The damaged myocardial cells that accumulated iodine showed drastic alteration of intracellular sodium-potassium ratio, suggesting the loss of cellular membrane integrity and probably irreversible cellular damage.…”
Section: Relationship Of Distribution Of Iodine and "9mtc-pyp To Resimentioning
confidence: 99%